Rekognisi Capaian Pembelajaran: Penelitian - Miftahul Marsena; Meli Sesmira; Jamilus (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This article discusses Recognition of Learning Outcomes (RPL), also known as Recognition of Prior Learning, as a strategic initiative to bridge the gap between individuals' actual competencies acquired through non-formal, informal, and work experiences and formal higher education qualifications. Supported by Minister of Education, Culture, Research, and Technology Regulation No. 41 of 2021, RPL aims to provide academic recognition and expand access to education for experienced individuals, in line with the concept of lifelong learning. The implementation of RPL is closely related and integrated with the Outcome-Based Education (OBE) approach, where recognition is not based on the learning process, but rather on evidence of outcomes demonstrating competency equivalence with the Graduate Learning Outcomes (CPL) of the study program. However, this implementation faces challenges in Quality Assurance, which must be addressed through a strong institutional role, transparent, fair, and reliable assessment procedures, and the professionalism of RPL Assessors to maintain the credibility of recognition results and academic integrity.